Molecular detection of Infectious canine hepatitis in a dog - Lalrinkima; Ashraf Wani, Muntasir; Moqbool, Yaqoota; Lalawmpuii, K; Ahmad Shah, Zubair; Narayan Mohanty, Rabi; Patro, Debananda (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
A 7 year old male Labrador breed of dog was presented at Veterinary Clinical Complex, SOA, (DU) with a history of inappetance, vomition, black stools and tick manifestation with no history of vaccination. Clinical examination revealed yellowish mucous membrane with dark yellow urination. Based on the clinical report there was higher level of liver enzyme ie. ALT (Alanine Aminotransferase) 125 μ/L, ALP (Alkaline phosphatase) 435 μ/L. During treatment the animal collapsed and died and the carcass was brought to the Department of Veterinary Pathology, IVS&AH for postmortem examination. On necropsy, external examination revealed icteric mucous membrane. Liver was enlarged, hemorrhagic with mottled appearance. Gall bladder was thickened and distended. There was shrinkage on both sides of the kidney and the surface was rough. Histopathological examination of the liver revealed hepatocellular necrosis with presence of intranuclear inclusion bodies. Molecular detection was carried out by PCR using gene based primers and revealed the product size of 508 bp. The findings from molecular detection confirmed that the dog was suffering from infectious canine hepatitis.